Assessing the Moderating Role of Customer Orientation on the Impact of Business Intelligence Tools on Digital Marketing Strategy Optimization - Salah, Ashraf H.; Alzghoul, Amro (International Review of Management and Marketing, 2024)
This research examines the interplay between Business Intelligence tools and digital marketing strategy optimization, with a focus on the moderating role of customer orientation. Utilizing a quantitative research design, the study explores how BI tools enhance digital marketing strategies and how customer orientation amplifies this effect among 207 respondents from the Jordanian telecommunications sector, reflecting a diverse range of experiences and perceptions within the industry. Through Structural Equation Modeling - Partial Least Squares (SEM-PLS), based on a stratified sample of these employees, the results confirmed that BI tools positively influence digital marketing strategy optimization. Additionally, customer orientation was found to significantly moderate this relationship, highlighting the importance of aligning technological capabilities with a customer-centric approach. The findings contribute valuable insights to marketing and business intelligence fields, suggesting strategies for organizations to enhance their market competitiveness and customer satisfaction, underpinned by a substantial engagement rate from the targeted demographic.